Comparative Analysis of Pre and Post merger: Effect on the Financial Performance of Microfinance Institution in Nepal - Singh, Silvia; Singh, Anushka; Nakarmi, Samyak; Shrestha, Icchya; Ghimire, Subigya; Sainju, Gaurav (New Perspective: Journal of Business and Economics, 2023)
There are no specific studies available on the impact of mergers and acquisitions on the financial performance of Microfinance Institutions in Nepal. Other studies available on the impact of funds and investments on the financial performance of organizations However, these studies are not directly related to the impact of mergers and acquisitions on the financial performance of Microfinance Institutions in Nepal. This study aims to analyze the effect of pre and post-merger financial performance of Microfinance Institutions (MFIs) in Nepal. The study has taken four merged Microfinance Institutions of Nepal as the sample. The study has used paired sample t-tests to analyze the data. The findings of the study showed that after the merger, the financial performance of the Microfinance Institutions in Nepal has not improved. The study found that there were no changes in the Earning per Share, Return on Equity, Return on Asset, Net profit Margin, Current Ratio, Net interest Margin and Price to Earnings Ratio. However, the study has found out that the Debt to Equity ratio has increased after the merger process. There are several studies available on the impact of mergers and acquisitions on the financial performance of banks in Nepal.